ANXIETY LEVELS AND INSOMNIA OF JOBLESS INDIVIDUALS IN SUMBERSARI DISTRICT, JEMBER REGENCY - Budiman, M. Elyas Arif; Yuhbaba, Zidni Nuris; Sutrianingsih, Yeni; Sya'id, Achmad (Jambura Nursing Journal, 2025)
Background: Unemployment is one of the social issues that occurs in many countries, including Indonesia. Often the health condition of unemployment is ruled out because it is more concerned with economic and social factors, even though health problems in unemployment are quite serious and can have other aspects. Health problems that often appear in unemployment are insomnia and anxiety, insomnia and anxiety need to get more attention. The impact of insomnia is anxiety disorders, stress, fatigue, attention disorders, concentration and memory, etc. Objective : analyze the relationship between the level of anxiety and insomnia in individuals who do not have a job in Sumbersari District, Jember Regency. Method: this research uses a correlational method with quantitative research design using a Cross Sectional approach. The population in this study was 36,882 unemployed in Sumbersari District. The sampling technique uses the slovin formula so that a total of 100 respondents are obtained. Sampling technique using Purposive Sampling. The research instrument used the TMAS (Taylor Manifest Anxiety Scale) anxiety questionnaire and the KSPBJ-IRS questionnaire (insomnia rating scale. This research uses the Spearman Rank correlation test. Results: the study found p vallue (